Assessment of Water Quality Using Macrobenthos as Bioindicators in Pier 2 Kota Agung, Tanggamus Regency - Suci Wulan Pawhestri; Andandaningrum, Della; Arrumaisha Vina Yofanka (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2026)
Kota Agung Pier 2 in Tanggamus Regency is a coastal area with high port activities that may affect aquatic environmental conditions. Previous studies on macrobenthos diversity in this area are limited, highlighting the need for updated ecological assessments. This study aimed to evaluate macrobenthos diversity as a bioindicator of water quality using a quantitative descriptive method across three observation stations. At each station, five sampling points with three replicate core samples (10 cm diameter, 10 cm depth) were collected during low tide in May 2025, ensuring consistent environmental conditions. The parameters measured included macrobenthos composition, temperature, depth, water clarity, pH, and dissolved oxygen (DO). Macrobenthos identified included the families Terebellidae, Ophiuridae, Conidae, and Mytilidae. Shannon-Wiener diversity (H′) ranged from 0.29–0.35 (low), evenness (E) from 0.04–0.05, and Simpson’s dominance (C) from 0.28–0.87, reflecting environmental stress and uneven species distribution. The Family Biotic Index (FBI) ranged from 3.81–3.86, indicating good water quality with low organic pollution. Physical and chemical parameters were within the standards set by Government Regulation No. 22 of 2021. Overall, the results show that while macrobenthos communities experience environmental pressures, the water at Pier 2 Kota Agung still supports aquatic life. This study provides updated data for ecological monitoring and informs sustainable coastal management